2022
DOI: 10.3390/polym14224874
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Effect of the Mechanism of Organic Polymers on Pellet Properties for Iron Ore Beneficiation

Abstract: Iron ore pellets not only have excellent metallurgical and mechanical properties but are also essential raw materials for improving iron and steel smelting in the context of the increasing global depletion of high-grade iron ore resources. Organic polymers, as important additive components for the production of high-quality pellets, have a significant impact on the formation as well as the properties of pellets. In this review, the mechanisms of organic polymers on the pelletizing properties, bursting temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that replacing or partially replacing bentonite with organic binders is feasible. However, due to their high cost and thermal instability, they are not widely utilized [8][9][10][11] . The use of low-cost solid waste as binder raw materials is also a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that replacing or partially replacing bentonite with organic binders is feasible. However, due to their high cost and thermal instability, they are not widely utilized [8][9][10][11] . The use of low-cost solid waste as binder raw materials is also a research hotspot.…”
Section: Introductionmentioning
confidence: 99%